Ambient effects on the electrical conductivity of carbon nanotubes. (December 2015) - Roch, Aljoscha; Greifzu, Moritz; Talens, Esther Roch; Stepien, Lukas; Roch, Teja; Hege, Judith; Van Nong, Ngo; Schmiel, Tino; Dani, Ines; Leyens, Christoph; Jost, Oliver; Leson, Andreas
Abstract: We show that the electrical conductivity of single walled carbon nanotubes (SWCNT) networks is affected by oxygen and air humidity under ambient conditions by more than a magnitude. Later, we intentionally modified the electrical conductivity by functionalization with iodine and investigated the changes in the band structure by optical absorption spectroscopy. Measuring in parallel the tubes electrical conductivity and optical absorption spectra, we found that conduction mechanism in SWCNT is comparable to that of intrinsically conducting polymers. We identified, in analogy to conducting polymers, in the infrared spectra a new absorption band which is responsible for the increased conductivity, leading to a closing gap in semiconducting SWCNT. We could show that by different functionalizations of the same SWCNT starting material the properties like conductivity can be dramatically changed, leading to different imaginable applications. We investigated here, an ultraviolet sensor with weakly modified SWCNT.